2018
DOI: 10.1136/bmjopen-2017-018826
|View full text |Cite
|
Sign up to set email alerts
|

Do quality improvement initiatives for diabetes care address social inequities? Secondary analysis of a systematic review

Abstract: BackgroundSocially disadvantaged populations carry a disproportionate burden of diabetes-related morbidity and mortality. There is an emerging interest in quality improvement (QI) strategies in the care of patients with diabetes, however, the effect of these interventions on disadvantaged groups remains unclear.ObjectiveThis is a secondary analysis of a systematic review that seeks to examine the extent of equity considerations in diabetes QI studies, specifically quantifying the proportion of studies that tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Also, many of them had chronic hypertension, which should alert caregivers to the increased risk of diabetes [22]. People of a lower socioeconomic status frequently experience a delay in their diabetes diagnosis and receive a lower level of care [21]. The women in our study with undiagnosed type 2 diabetes were also more likely to be immigrants compared with those with diagnosed pre-pregnancy diabetes.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Also, many of them had chronic hypertension, which should alert caregivers to the increased risk of diabetes [22]. People of a lower socioeconomic status frequently experience a delay in their diabetes diagnosis and receive a lower level of care [21]. The women in our study with undiagnosed type 2 diabetes were also more likely to be immigrants compared with those with diagnosed pre-pregnancy diabetes.…”
Section: Discussionmentioning
confidence: 73%
“…Our study found that more women with undiagnosed type 2 diabetes were in the lowest socio-economic quintile than any other group, including those previously diagnosed with pre-existing diabetes. It is known that people of lower socioeconomic status are more likely to have higher rates of diabetes [21]. The women in our study with undiagnosed type 2 diabetes were just as likely to have a primary care physician and also had more visits to their primary care physician prior to pregnancy then those with GDM alone, and therefore this represents missed opportunities for a diabetes diagnosis pre-pregnancy.…”
Section: Discussionmentioning
confidence: 82%
“…However, their benefits may be more apparent in higher SES groups who possess the resources to facilitate their use [26]. A recent systematic review found that fewer than one-third of quality improvement trials included equity-relevant considerations, limiting their application to disadvantaged groups [27]. Ensuring that quality improvement initiatives consider their effects across socio-economic groups will help to ensure interventions are appropriate and will not inadvertently exacerbate inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…To explore health inequalities, we focused on indicators of social disadvantages defined by PROGRESS [19,41]. Most of social factors were identified in the baseline patient characteristics.…”
Section: Equity Analysismentioning
confidence: 99%